The mental health impact of the covid-19 pandemic on healthcare workers, and interventions to help them: A rapid systematic review. (November 2020) - Muller, Ashley Elizabeth; Hafstad, Elisabet Vivianne; Himmels, Jan Peter William; Smedslund, Geir; Flottorp, Signe; Stensland, Synne Øien; Stroobants, Stijn; Van de Velde, Stijn; Vist, Gunn Elisabeth
Highlights: Healthcare workers' mental health problems correlate with organizational factors such as workload and exposure to covid-19 patients. Healthcare workers are more interested in occupational protection, rest, and social support than in professional psychological help. Interventions focus more on addressing individual psychopathology, which points towards a mismatch between what workers want and need, and the services available to them. Abstract: The covid-19 pandemic has heavily burdened healthcare systems throughout the world. We performed a rapid systematic review to identify, assess and summarize research on the mental health impact of the covid-19 pandemic on HCWs (healthcare workers). We utilized the Norwegian Institute of Public Health's Live map of covid-19 evidence on 11 May and included 59 studies. Six reported on implementing interventions, but none reported on effects of the interventions. HCWs reported low interest in professional help, and greater reliance on social support and contact. Exposure to covid-19 was the most commonly reported correlate of mental health problems, followed by female gender, and worry about infection or about infecting others. Social support correlated with less mental health problems. HCWs reported anxiety, depression, sleep problems, and distress during the covid-19 pandemic. We assessed the certainty of the estimates of prevalence of these symptoms as very low using GRADE. Most studies did not report comparative data on mental health symptoms before the pandemic or in the general population. There seems to be a mismatch between risk factors for adverse mental health outcomes among HCWs in the current pandemic, their needs and preferences, and the individual psychopathology focus of current interventions.